DOI: 10.2969/aspm/07710035
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic problems in structural equation modeling

Abstract: The paper gives an overview of recent advances in structural equation modeling. A structural equation model is a multivariate statistical model that is determined by a mixed graph, also known as a path diagram. Our focus is on the covariance matrices of linear structural equation models. In the linear case, each covariance is a rational function of parameters that are associated to the edges and nodes of the graph. We statistically motivate algebraic problems concerning the rational map that parametrizes the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 43 publications
(73 reference statements)
0
32
0
Order By: Relevance
“…Ho & Nguyen (2016) proposed a general algebraic statistics framework for singular finite-mixture models, and showed that the optimal convergence rate for skewednormal mixtures is n −1/12 . More generally, singular learning theory is studied in (Watanabe, 2009(Watanabe, , 2013, and the algebraic structures of Gaussian mixture/graphical models and structural equation models are explored in (Leung et al, 2016;Drton et al, 2011;Drton, 2016).…”
Section: Related Workmentioning
confidence: 99%
“…Ho & Nguyen (2016) proposed a general algebraic statistics framework for singular finite-mixture models, and showed that the optimal convergence rate for skewednormal mixtures is n −1/12 . More generally, singular learning theory is studied in (Watanabe, 2009(Watanabe, , 2013, and the algebraic structures of Gaussian mixture/graphical models and structural equation models are explored in (Leung et al, 2016;Drton et al, 2011;Drton, 2016).…”
Section: Related Workmentioning
confidence: 99%
“…Second, even though spectral methods are often less refined, the graph-theoretic approach cannot easily address parameter-dependent behavior; in particular, the unique effect of the SNR we observed in our simulations (and noted in (Balakrishnan et al 2017)). Currently, there is very little we are able to say about the impact of the SNR, and a combined approach might be more fruitful (Drton 2018).…”
Section: Discussionmentioning
confidence: 99%
“…, p}, i ∈ J and j ∈ J, let β i|J = (Σ iJ Σ −1 JJ ) t denote the vector of regression coefficients of X i on X J , with its j-th entry being β ij|J , the coefficient corresponding to variable X j . We may equivalently write the statistical model for X as a system of recursive linear regression equations (also called a linear structural equation model [22]), where for each i ∈ {1, . .…”
Section: A the Inverse Covariance Matrix And Systems Of Recursive Rementioning
confidence: 99%